EFFECT OF GARDEN CRESS (LEPIDIUM SATIVUM ) ON MITOTIC INDEX AND FORMATION OF MICRONUCLEI IN WHITE MICE BONE MARROW CELLS - Ilham A. Khalaf (Mesopotamia Journal of Agriculture)
The effect of garden cress ( Lepidium sativum ) on mitotic index (MI) and formation of micronuclei (Mn) in bone marrow cells of white mice was studied , in addition to the study of the counter effect of plant juice on MI disruption and Mn induction by cyclophosphamide (Cp) . The results indicated that Cp reduced the MI to level of positive control after 2 , 4 , 6 days with significant differences compared to the negative control (P<0.01) , while the plant juice 0.1 , 0.25 , 0.5 ml / animal administrated orally had no effect and the MI values were similar to the negative control. Oral administration of juice before administration of the mutagen (R/Cp) or with the mutagen (R+Cp) helped the tissues to preserve their MI values at natural level. Administration of juice after the mutagen (Cp/R) resulted in reduction of MI values compared to the natural values with statistical significant difference (P<0.01)